The Principles of Islam and Their Impact On the Upbringing of Adolescents and the Formation of Their Personalities: مبادئ الإسلام وأثرها في تنشئه المراهقين وتكوين شخصياتهم - Salh Abdul Rahim Hamei, Amna; Musal Kassim, Sayyid Buhar; Yusof, Muhammed (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2022)
The study aims to identify the principles of Islam and their impact on the upbringing of adolescents and the formation of their personalities. The problem of the study lies in the absence of applying the principles of Islam and following what Allah has commanded in the Holy Quran and the Prophet's purified Sunnah. The importance of the study is highlighting the principles of Islam and their impact on the upbringing of adolescents and the formation of their personalities. The study followed the descriptive and analytical approach to describe and analyze the principles of Islam and their impact on the upbringing of adolescents and the formation of their personalities, and the study also followed the inductive approach to extrapolate the texts of the Holy Quran and the Prophet's purified Sunnah that were received regarding the upbringing of adolescents and the formation of their personalities. The study has reached many results, including that Allah the Almighty has ordered to pay attention of adolescents and to teach them sports to take care of their general health. Results showed also that Allah, the Almighty has ordered Muslims to be very interested in for knowledge which is the only way that contributes clearly and concretely to the formation of the personalities of adolescents. Results showed also that Allah the Almighty has ordered to preserve the time, which is the basis of the life in which we live. The study also showed that the upbringing of adolescents needs more patience and containment in compliance with the commands of Allah the Almighty regarding taking care of them. The study has recommended that there is a need to pay attention to adolescents and benefit from their abilities and energies in the demand for knowledge and work significantly. The study also recommended that there is a need to continue training parents on how to deal with adolescents through the advice adopted by psychologists and specialists in Islamic education affairs.